The Role of Medicinal Plants Extras in Lowering the Level Blood Sugar Level - Diana Essam Kazem Obaid; Nour Imad Khalil Nasser; Ali Amer Kareem Jiyad; Kawthar Kazem Jabbara mazeel; zahraa abd al rahem sultan batol (Genius Journals, 2024)
Recently, some medicinal plants have been reported to be useful in diabetes worldwide and have been used empirically in antidiabetic and antihyperlipidemic remedies. Antihyperglycemic activity of the plants is mainly due to their ability to restore the function of pancreatic tissues by causing an increase in insulin output or inhibit the intestinal absorption of glucose or to the facilitation of metabolites in insulin dependent processes. More than 400 plant species having hypoglycemic activity have been available in literature, however, searching for new antidiabetic drugs from natural plants is still attractive because they contain substances which demonstrate alternative and safe effects on diabetes mellitus. Most of plants contain glycosides, alkaloids, terpenoids, flavonoids, carotenoids, etc., that are frequently implicated as having antidiabetic effect.
Keywords: medicinal plants; diabetes